A COMPARISON OF MORBIDITY AND MORTALITY AMONG EARLY, MODERATE AND EXTREME PREMATURE INFANTS REPORTING IN GILGIT - Jehanzeb, Kanwal; Shah, Sajid Ali; Zaman, Saeed; Haq, Zia Ul; Lodhi, Munir Akmal; Ashraf, Nadeem (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the morbidity and mortality among early, moderate and extreme premature infants reporting in Gilgit.Study Design: Comparative cross sectional study. Place and Duration of Study: Neonatal intensive care unit, Combined Military Hospital, Gilgit, from Jun 2017 to Jun 2018.Methodology: Patients who had completed antenatal visits in Gynae dept and delivered premature babies were recruited in this study. Premature babies from 34 to 37 weeks of gestation are termed as late preterm, 32 to